Recent Poetry and the Essential Word - Biruté Ciplijauskaité (Studies in 20th & 21st Century Literature, 1992)
Postmodern poetry resists classification in tight compartments. After the last artificially-named group of the novisimos in the 60s, the evolution of poetry in Spain has followed different and at times divergent paths. The novisimos had reacted against "social" poetry, denouncing its lack of attention to artistry, almost prosaic quality, subservience to theme, and produced elaborate creations with an emphasis on form and the exquisite and more hermetic word and subject. Obeying the law of corsi e ricorsi, there was a certain return in the 80s to simpler expression which, however, does not pretend to be that of the "man on the street" reflecting the historical circumstance, but rather a search for essences, for eternal values. Each poet—M.V. Atencia, Jesus Munarriz, and Luis Suñen can serve as examples of the "essential" inclination—traces his own way and creates a personal poetics. Faith in the word is their common denominator. This turn to simplicity can also be observed in the last works of such poets as Carvajal, Gimferrer and Siles, who admit, however, greater ambiguity of word and intention.
Keywords: Spanish poetry; Novismos; evolution of poetry; poetic evolution; corsi e ricorse; M.V. Atencia; Jesus Munarriz; Luis Suñen; word; language; Carvajal; Gimferrer; Siles